PRESUPPOSITION TRIGGERS - A COMPARATIVE ANALYSIS BETWEEN ORAL NEWS AND WRITTEN ONLINE NEWS DISCOURSE - Luthfiyatun Thoyyibah (Universitas Galuh, 2017)
Information becomes a crucial thing that someone gets in everyday terms. Dealing with the digital era, people can get the information through any communication devices. Then, language still has its own rule in communication. As part of linguistic features, the notion of presupposition and its triggers have been studied by many scholars, linguists and philosophers, but as far as the researcher knows, the comparison between presupposition triggers on news broadcast and online transcript has not been explored yet. Therefore, the present research tries to identify the main presupposition triggers used in both transcripts. This is a descriptive qualitative study where it is designed to describe the case of the study by words or sentences rather than numbers. The object of the study is presupposition found in both CNN different news style. Accordingly, two transcripts were analyzed in terms of presupposition triggers, namely existential, factive, lexical, non-factive, structural, counter-factual, adverbial, and relative. The analyses of the transcripts revealed that the most frequently used presupposition trigger in both varieties of oral discourse was existential. It refers to the ability of existential presupposition in diverting attention to other parts of the sentence or utterance. Keywords: presupposition, triggers, presupposition triggers, discourse